(untitled) (Homoeopathy for All, 2025)
Introduction: Renal calculi, hydroureteronephro sis, fatty liver, and adenomyosis are common yet clinically challenging conditions, particularly when occur ring concurrently in postmenopausal women. Conventional treatment often involves surgical or pharma cological interventions. This case report highlights the role of indi vidualized homoeopathic manage ment in addressing this multisystem presentation. Case Summary: A 50-year-old postmenopausal woman with bilateral renal calculi, hydroureteronephrosis, fatty liver, and adenomyosis presented with abdominal pain, pelvic heaviness, flank pain, and vertigo. Based on her totality of symptoms, Phosphorus was prescribed. Over two months, she showed marked clinical and radiological improvement. This case highlights the potential of individualized homoeopathic treatment in managing complex multisystem conditions.